Introducing big data: A data management perspective for newbies - Emran, Nurul Akmar (Penerbit UTeM Press, 2024)
Developing any applications that involve the storage and management of big data requires an application developer to carefully build design plans to produce high-quality and useful products. Many approaches can be adopted to explain database management that needs to adapt to the rapidly developed and changing database technology. As a result, the way to describe database management should be updated to reflect the current and latest database technology. This book is written with the aim to introduce the readers to basic knowledge of big data management and its modelling. Key features include topics on: The complexity of big data and its characteristics that eventually calls for specific data management solutions. Challenges in big data management Big data management functions and technologies Big data lifecycle concepts. Traditional data models that consist of relational, object-relational, hierarchy, and network data models. NoSQL data models that consist of key-value, document-based, columnar, and graph data models.